1996
DOI: 10.1159/000177076
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Use and Clinical Utility of Exercise Thallium-201 Single Photon Emission-Computed Tomography in a Community Hospital

Abstract: Single photon emission computed tomographic (SPECT) imaging with thallium-201 was evaluated in 492 consecutive, unselected patients to ascertain the patterns of use and additive value to the exercise electrocardiogram in the diagnosis of myocardial ischemia in a community hospital setting. Myocardial perfusion images were interpreted by a single observer employing visual and confirmatory quantitative analysis. The majority of patients (69%) were studied to evaluate the functional consequences of known coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…1112,14,2441 In this analysis, the referral rates after normal and abnormal exercise tests were 4.1% (95% CI, 2.8% to 5.3%) and 43.7% (36.5% to 50.9%), respectively, with odds ratio for referral after an abnormal test of 14.3 (9.8 to 20.7). After adjusting for referral, the sensitivity of exercise ECHO and MPI fell to 34% (95% CI, 26% to 41%) and 38% (95% CI, 31% to 44%) and the specificity rose to 99% (95% CI, 99% to 100%) and 99% (95% CI, 99% to 100%), respectively.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…1112,14,2441 In this analysis, the referral rates after normal and abnormal exercise tests were 4.1% (95% CI, 2.8% to 5.3%) and 43.7% (36.5% to 50.9%), respectively, with odds ratio for referral after an abnormal test of 14.3 (9.8 to 20.7). After adjusting for referral, the sensitivity of exercise ECHO and MPI fell to 34% (95% CI, 26% to 41%) and 38% (95% CI, 31% to 44%) and the specificity rose to 99% (95% CI, 99% to 100%) and 99% (95% CI, 99% to 100%), respectively.…”
Section: Resultsmentioning
confidence: 72%
“…Of these 107 studies, 17 reported referral patterns after normal or abnormal exercise tests and were included in our analysis. 1112,14,2441 The characteristics of these studies and their 49 006 participants are shown in Table 1. The mean age was 60.7 years, 39.6% were women, 0.8% had a prior history of myocardial infarction (reported in 13 studies), and 0.1% had a prior history of revascularization (reported in 14 studies).…”
Section: Resultsmentioning
confidence: 99%